Application of infraorbital rim augmentation with pocket fat filling to correct tear trough deformity - Liu, Yukun; Wang, Yi; Cai, Changqi; Wu, Xiuying; Wang, Haiping (Frontiers in Surgery, 2023)
Background Tear trough deformity is one of the most common complaints in clinical settings. The correction of this groove is challenging in facial rejuvenation. The lower eyelid blepharoplasty varies with different conditions. A novel approach of using orbital fat in the lower eyelid to increase the volume of the infraorbital rim with granule fat injection has been applied in our institution for more than 5 years. Objectives This article aims to describe the detailed steps of our technique and verify its effectiveness by a cadaveric head dissection after surgical simulation. Methods In this study, a total of 172 patients with tear trough deformity underwent lower eyelid orbital rim augmentation with fat filling in the sub-periosteum pocket. According to Barton's grades, 152 patients underwent lower eyelid orbital rim augmentation with orbital fat filling, 12 patients had it combined with autologous granule fat from other body parts, and 8 patients received only transconjunctival fat removal to correct tear trough. Results The modified Goldberg score system was used to compare preoperative and postoperative photographs. Patients were satisfied with the cosmetic results. Excessive protruding fat was released, and the tear trough groove was flattened by using autologous orbital fat transplantation. The lower eyelid sulcus deformities were well-corrected. To further illustrate the anatomical structure of the lower eyelid area and injection layers, six cadaveric heads were used for surgical simulation and demonstrated the effectiveness of our technique. Conclusions This study indicated that the infraorbital rim could be increased by transplanting orbital fat to the pocket, which was dissected under the periosteum, and the procedure has been verified as reliable and effective. Evidence-based medicine (EBM) level Level II.